Des corpus vidéo pour la formation des enseignants de langue - Catherine Muller; Catherine David; Elsa Crozier (Recherches en didactique des langues et des cultures)
This article deals with an ongoing research project about the use of video of classroom interaction for the training of French language teachers. In order to help students better understand the teaching activity, stimulated recall interviews were conducted with the teachers filmed. We seek to demonstrate how the teachers’ discourse about their practices, which gives access to obstacles encountered and to strategies implemented, can prove to be useful in pre-service and in-service teacher education. The project is first set in the broader context of the research on teacher cognition and teacher education. Then we present the approach implemented, in which the involvement of teachers plays an important role, and the methodological issues that have emerged until now. The paper ends with the analysis of the extracts regarded as relevant for the three components of the project: pre-service teacher education, in-service teacher education, and research.